Optimization of combustion chamber geometry for natural gas engines with diesel micro-pilot-induced ignition. (15th August 2016) - Wang, Bin; Li, Tie; Ge, Linlin; Ogawa, Hideyuki
Highlights: Combustion chamber geometry is optimized to reduce the HC/CO emissions. CFD model is calibrated against the spray visualization and engine bench test data. Design space is explored by the multi-objective NSGA-II with Kriging meta-model. HC and CO emissions are respectively reduced by 56.47% and 33.55%. Abstract: Smokeless, low nitrogen oxides (NOx), and high thermal efficiency have been achieved through the lean-burn concept for natural gas engine with diesel micro-pilot-induced ignition (MPII). However, the combustion chamber is usually not specialized for natural gas combustion, and increases in the unburned hydrocarbon (HC) and carbon monoxide (CO) emissions are still a challenge for this type of engines. This paper describes optimization of the combustion chamber geometry to reduce the HC and CO emissions and improve the combustion efficiency in the MPII natural gas engine. The 3-D computational fluid dynamics (CFD) simulation model coupled with a chemical reaction mechanism is described. The temporal development of the short-pulsed diesel spray in a high pressure constant-volume vessel is measured and used to calibrate the spray model in the CFD simulation. The simulation models are validated by the experimental data of the in-cylinder pressure trace, apparent heat release rate (AHRR) and exhaust gas emissions from a single-cylinder MPII natural gas engine. To generate the various combustion chamber geometries, the bowl outline is parameterized by the two cubic Bezier curves while keeping the compression ratio constant. The available design space is explored by the multi-objective non-dominated sorting genetic algorithm II (NSGA-II) with Kriging-based meta-model. With the optimization, the HC and CO emissions are reduced by 56.47% and 33.55%, respectively, while the NOx emissions, the maximum rate of pressure rise and the gross indicated thermal efficiency that are employed as the constraints are slightly improved. Finally, the mechanism of the reduction in HC and CO emissions with the optimized combustion chamber geometry is investigated and discussed in details.